2017
DOI: 10.7812/tpp/16-066
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Physician Coaching Pilot to Promote Value-Based Referrals to Specialty Care

Abstract: This physician mentoring program aimed at reducing specialty referral rates is feasible and acceptable in primary care settings. Increasing the appropriateness of referrals has the potential to provide patient-centered care, reduce costs for the system, and improve physician satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Sample sizes of the studies ranged widely from four to 1,559 participants. This included six studies that included ten or fewer participants; often, these were qualitative interviews assessing the experiences of individual participants with the peer-to-peer interventions (Tuzzio et al, 2017;Reyes Ortega et al, 2019;Agarwal, Brooks and Greenberg, 2020;Schwartz et al, 2020;Barron, Abdallah and Heltne, 2017;Boyle and Kochinda, 2004;Fox, 2010). We also identified four studies that reported on more than 1,000 participants that had access to the program (Tamers et al, 2011;Pisarski et al, 2006;Greenberg et al, 2010;.…”
Section: Evidence Map Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sample sizes of the studies ranged widely from four to 1,559 participants. This included six studies that included ten or fewer participants; often, these were qualitative interviews assessing the experiences of individual participants with the peer-to-peer interventions (Tuzzio et al, 2017;Reyes Ortega et al, 2019;Agarwal, Brooks and Greenberg, 2020;Schwartz et al, 2020;Barron, Abdallah and Heltne, 2017;Boyle and Kochinda, 2004;Fox, 2010). We also identified four studies that reported on more than 1,000 participants that had access to the program (Tamers et al, 2011;Pisarski et al, 2006;Greenberg et al, 2010;.…”
Section: Evidence Map Resultsmentioning
confidence: 99%
“…In a second step, we tested the content validity and usability of the framework. For this step, we abstracted framework elements from a subset of publications (Beckman et al, 2012;Chen et al, 2016;Dyess and Parker, 2012;Eagle, Creel, and Alexandrov, 2012;Edrees et al, 2016;El Hechi et al, 2020;Fornari et al, 2018;Fox, 2010;Graham et al, 2019;Gray-Toft and Anderson, 1983;Lewis et al, 2017;Marks et al, 2017;Mayer et al, 2014;McDermott, Brook, and Ben-Isaac, 2017;Merandi et al, 2017;Mills and Mullins, 2008;Mundt, 2001;Olson et al, 2016;Olson et al, 2015;Palamara et al, 2015;Peterson et al, 2008;Pololi et al, 2002;Ripp, Fallar, and Korenstein, 2015;Rohatinsky, Cave, and Krauter, 2020;Schwartz et al, 2020;Shanafelt et al, 2017;Shoji, Benight, and Stearns, 2016b;Tuzzio et al, 2017). The selected publications used to test the developed framework all addressed interventions, and these were evaluated in a broader health care setting.…”
Section: Professional Peer-to-peer Support Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…A mixed methods study by Tuzzio et al examined the impact of education at the interface in the form of “peer coaching” on specialty referrals (Tuzzio et al , 2017). All participants reported benefit of peer discussion on patient care.…”
Section: Resultsmentioning
confidence: 99%